The influence of popular and delinquent adolescents on school delinquency: specifying the key delinquent models - Gallupe, Owen (Journal of crime and justice, 2017)
Prior research has shown evidence for the existence of a relationship between peer and individual delinquency. It is now important to specify the mechanisms by which that relationship operates. The contribution of the current study is to identify the adolescents who are likely to act as the key delinquent models. It is expected that in schools where a large percentage of adolescents are both highly popular and highly delinquent, levels of school delinquency are likely to be highest. Using data from 112 schools in the National Longitudinal Study of Adolescent to Adult Health, this study finds that, even when controlling for neighborhood and school characteristics (including the ratio of delinquent to non-delinquent students), schools with a greater percentage of highly popular/highly delinquent students have significantly greater levels of delinquency.